2021
DOI: 10.1080/23766808.2021.1920296
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding approach to characterize microalgae isolated from freshwater systems in Ecuador

Abstract: The use of suitable DNA barcodes and the generation of databases with reference sequences have been considered a promissory approach for the identification of Chlorophyta and Cyanophyta microalgae. In this study, we carried out a molecular characterization and identification of strains isolated from freshwater systems in Ecuador using a dual barcode method. The target sequences for Chlorophyta were 18S rDNA and rbcL genes, and 16S rDNA and 16S-23S rDNA intergenic spacer (ITS) for Cyanophyta. We reported these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…The closest match to the cyrE2 sequence at the GenBank was 98% identity to cyrE related to Aphanizomenon sp., which has been described as a benthic cyanobacterium genus (Gaget et al, 2017). In South America, most isolated strains from R. raciborskii are reported to produce saxitoxins (Hoff-Risseti et al, 2013), although CN producers have also been found in Brazil and Venezuela (Antunes et al, 2015;Mowe et al, 2015), and Ecuador (Ballesteros et al, 2021;Van Colen et al, 2017;Venegas et al, 2018). Even though R. racibosrkii has been reported in Yahuarcocha and San Pablo in association with the presence of CN (Van Colen et al, 2017), cyrJ was not amplified from samples in these water bodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The closest match to the cyrE2 sequence at the GenBank was 98% identity to cyrE related to Aphanizomenon sp., which has been described as a benthic cyanobacterium genus (Gaget et al, 2017). In South America, most isolated strains from R. raciborskii are reported to produce saxitoxins (Hoff-Risseti et al, 2013), although CN producers have also been found in Brazil and Venezuela (Antunes et al, 2015;Mowe et al, 2015), and Ecuador (Ballesteros et al, 2021;Van Colen et al, 2017;Venegas et al, 2018). Even though R. racibosrkii has been reported in Yahuarcocha and San Pablo in association with the presence of CN (Van Colen et al, 2017), cyrJ was not amplified from samples in these water bodies.…”
Section: Resultsmentioning
confidence: 99%
“…To check the success of the DNA extraction and the absence of inhibition in the PCR reaction, the amplification of the region 16S rDNA gene was carried out as a positive control using the primers CYA106F / CYA781R (Nübel et al, 1997) and PCR conditions, as outlined by Ballesteros et al (2021). eDNA samples with a positive amplification for the 16S were considered suitable for further analysis.…”
Section: Nested-pcr Analysesmentioning
confidence: 99%
“…ITS2 DNA barcoding identifies short region genes with efficient DNA barcodes, 700 base pairs in one partial gene region. (Ballesteros et al, 2021).…”
Section: Pcr Amplification Of Its2 Rdnamentioning
confidence: 99%
“…Microalgae identification can also be made through the molecular level analysis of conserved regions of the DNA, such as Ribulose Bisphosphate Carboxylase Large subunit gene (rbcL), 16S and 18S ribosomal RNA (rRNA) genes used for the profiling of prokaryotic and eukaryotic microalgae [15][16][17]. The reference database to align the sequenced results is equally important to the DNA barcodes sequenced.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of enrichment media on microalgae population growth and diversity in the literature remains elusive; however, still utilized [17,[22][23][24]. We previously investigated the efficiency of the commonly used BG-11 and BBM in microalgae enrichment for diversity identification and the effect of vitamin enrichment and reduced media nutrient on diversity enrichment.…”
Section: Introductionmentioning
confidence: 99%